Perfil inflamatório em cães com doença mixomatosa da valva mitral - Camacho, Rafael Rodrigues [UNESP] (2017)
Inflammatory substances such as interleukins (IL), tumor necrosis factor alpha (TNF-α) and C-reactive protein (CRP) have been demonstrated to play a role in heart failure progression. The aims of this study were two-fold: to investigate the concentration of circulating cytokines in dogs with myxomatous mitral valve disease (MMVD) in different stages, and to assess the relationship between these substances and cardiac morphology and function. For this purpose, twelve dogs with MMVD (7 stage-B2; 5 stage-C) and nine healthy controls underwent a transthoracic echocardiogram and had their serum concentrations of IL-1β, 4, 6, 10, TNF-α and CRP assessed. Data was submitted to Shapiro-Wilk normality test, groups were compared with ANOVA or Krukal-Wallis test according to distribution, and correlation coefficients were obtained with Spearman test. The IL-1β levels were different (P: 0.0056) between groups. Also, a positive correlation existed between IL- 1β and left ventricular end-diastolic diameter (R: 0.56), left atrium-to-aorta ratio (R: 0.63) and echocardiography congestion surrogates. Similarly, IL-4 exhibited moderate-to-strong positive correlation with parameters of cardiac remodeling and congestion, while IL-6 was negatively correlated with the shortening fraction (R: -0.49). As the main conclusion, IL-1β levels increases in dogs with MMVD, and even higher levels are observed in overtly symptomatic animals.